(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
The Flores Fault is the one of caused an earthquake on August 5, 2018 in Lombok Island. It is reported that this earthquake with magnitude of 7.0 Mw caused a small tsunami with amplitude of 13.5 cm in the coastal area of Carik village, North Lombok. This study aimed to simulate a potential tsunami hazard from the Flores faults activity using the COMCOT v1.7 tsunami model which estimates potential tsunami height, tsunami arrival time, and potential tsunami affected areas. Historical earthquake data as an epicenter in the simulation was the earthquake on September 2, 2018, with the earthquake magnitude of 7 Mw. On the basis of the earthquake above, the model parameters was chosen, such as the depth of epicenter of 14 km, width fault area of ​​47.9 x 15.9 km, dislocation of 2.5 m, strike of 284o, slip of 64o, and dip of 88o. Simulation layer is divided into 3 layers based on nesting grid system with 464 m, 232 m and 77 m resolution, respectively. Bathymetric data were obtained from GEBCO with a 15-arc second grid size. Tsunami propagation simulation has been performed for duration of 30 minutes, which produced an initial tsunami height of 0.9 m. The maximum tsunami height revealed from the simulation was between 1-2.5 m on land. Estimated arrival time of the tsunami in North Lombok was ftom 3 to 13 minutes. Simulation result showed that sub-district area of Bayan, Kayangan, Tanjung, and Gangga are affected potentially areas by the tsunami. The maximum height and arrival time of the tsunami in North Lombok have the potential to be destructive and can cause casualties, so that mitigation efforts are needed, such as socialization and training in dealing with tsunami hazards, planting coastal vegetation that is suitable for the substrate on the coast, and building offshore breakwaters.